2020
DOI: 10.1002/marc.202070043
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Cationic Block Copolymer Brushes for Temperature‐Modulated Stem Cell Separation

Abstract: Front Cover: In article number 2000308 by Kenichi Nagase and co‐workers, functional thermoresponsive‐cationic block copolymer brushes are fabricated by two steps of surface‐initiated ATRP of N,N‐dimethylaminopropyl acrylamide and N‐isopropylacrylamide. All three types of tested cells adhere to the copolymer brush at 37 °C and selective detachment of mesenchymal stem cells from the copolymer brush occurs at 20 °C. Thus, the copolymer brush can be useful as an effective tool to separate stem cells from contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…20a). 258,259 These techniques could be used for 3D tissues. The cell sheet used for 3D stacking were obtained from a mold made by UV-cured polyurethane acrylate mixed with glycidyl methacrylate, followed by PNIPAAM grafting (Fig.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…20a). 258,259 These techniques could be used for 3D tissues. The cell sheet used for 3D stacking were obtained from a mold made by UV-cured polyurethane acrylate mixed with glycidyl methacrylate, followed by PNIPAAM grafting (Fig.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Many reports have compared the different strategies for cell block elaboration and some favor one method (collodion bag vs. HistoGel; microwave vs. room temperature, air dried sediment vs. formalin fixation, among others). 16,17 There is not enough evidence to favor one method over the rest, and the choice mainly depends on individual factors related to the local practice or the personal preferences. However, each laboratory must clearly know the advantages and limitations of the method they use to avoid over interpreting results that can bebiased by the technique.…”
Section: Cytological Samplesmentioning
confidence: 99%
“…showed that various types of cytological preparations can be used for EGFR mutation analysis: archived stained slides (Romanowsky or Papanicolaou-stained), liquid-based preparations and cell blocks. 17 Some studies comparing scraping cells from slides and the use of cell blocks showed similar high sensitivity rates with both techniques, but other studies found that cell scraping may reduce the accuracy of PCR-based tests. 21,26 In a previous report by Molina-Vila et al, the authors performed PCR in cytological samples and found a 100% sensitivity rate for detecting in-frame deletions in exon 19, L858R point mutations in exon 21 and the T790 mutation in exon 20, as compared with direct sequencing.…”
Section: Cytologymentioning
confidence: 99%
“…In this decade, thermoresponsive cationic brush surfaces have been investigated to develop smart cell separation systems for the purification of target cells (e.g. mesenchymal stem cells) from cell mixture without cell labelling [44,45]. These cell separations are known to be achieved because of the differences between individual cellular properties, including zeta potentials and cell adhesion/detachment behaviors.…”
Section: Cell Adhesion and Detachment Assaymentioning
confidence: 99%